Marketing information systems in the digital era (a literature review study) - Hadi Kurniawanto; Hafidz Hanafiah (Institute of Computer Science (IOCS), 2023)
The marketing information system is part of a management information system focusing on marketing. This information system is essential, especially in the digital era that depends on technology. In this research, we will focus on the trend of how marketing information systems are an option for some companies and the customer's perspective. This study uses qualitative studies from various recent journals. The study results show that most marketing information systems are still used to support the company's business with web-based information systems, with e-commerce as an option compared to Android-based ones. The other variables are still talking about customer satisfaction and loyalty. Use this information system used by several business fields, cooperatives, banking, property, entrepreneurship, tourism, agriculture, and sales as a decision by considering efficiency and effectiveness as well as long-term risks and effects.